2013
DOI: 10.1515/hsz-2013-0267
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a type D1A EUL-related lectin from rice expressed in Pichia pastoris

Abstract: OrysaEULD1A is one of the five EUL genes in rice (Oryza sativa) encoding a putative carbohydrate-binding protein belonging to the family of Euonymus related lectins (EUL). The OrysaEULD1A sequence comprises two highly similar EUL domains (91% sequence similarity and 72% sequence identity) separated by a 23 amino acid linker sequence and preceded by a 19 amino acid N-terminal sequence. In the present study, the full-length protein OrysaEULD1A as well as its individual domains OrysaEULD1A domain 1 and 2 were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…OsEULD2 was significantly upregulated after Magnaporthe infection. These results are in agreement with a previous qPCR study using different time points which also showed the upregulation of OsEULD1b and OsEULD2 after Xanthomonas infection and the upregulation of OsEULD2 after disease by Magnaporthe (Al Atalah et al, 2014). Transcript levels for OsEULD2 were significantly upregulated by three different rice pathogens.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…OsEULD2 was significantly upregulated after Magnaporthe infection. These results are in agreement with a previous qPCR study using different time points which also showed the upregulation of OsEULD1b and OsEULD2 after Xanthomonas infection and the upregulation of OsEULD2 after disease by Magnaporthe (Al Atalah et al, 2014). Transcript levels for OsEULD2 were significantly upregulated by three different rice pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…qRT-PCRs were performed using SYBR Green I Mix (Bio-Rad) and following conditions: 10 min initial denaturation step at 95°C, 42 cycles (15 s at 95°C, 25 s at 60°C, 20 s at 72°C) and detected with Bio-Rad CFX Connect™ Real-Time PCR Detection System. The expression of the genes was normalized against three reference genes: EXP (LOC_Os03g27010.1), EIF5C (LOC_Os011g21990.1), and EXP Narsai (LOC_Os07g02340.1) (Narsai et al, 2010;Kyndt et al, 2012;Al Atalah et al, 2014). The stability of the reference genes was checked by the qbase+ software (Biogazelle, Zwijnaarde, Belgium).…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…ArathEULS3 from A. thaliana preferentially interacts with N -glycans containing galactosylated structures such as Lewis X [Galβ1–4(Fucα1–3)GlcNAc], Lewis Y [Fucα1–2Galβ1–4(Fucα1–3)GlcNAc] and lactosamine (Galβ1–4GlcNAc) motifs (Van Hove et al, 2011). Similarly, both EUL domains composing the two-domain EUL protein from rice, OrysaEULD1A, show carbohydrate specificity toward galactose containing glycans (Al Atalah et al, 2014b). In contrast, the rice protein OrysaEULS2 preferably binds mannosylated N-glycan structures (Al Atalah et al, 2012).…”
Section: Pathogen Recognition Based On Protein–carbohydrate Interactionsmentioning
confidence: 99%
“…Besides Nictaba, which appears as the prototype of a group of closely related lectins [263,264], other groups of stress inducible lectins in the nucleocytoplasmic compartment have been identified, such as the Euonymus europaeus EUL-related lectins [170,265] and the group of mannose-binding jacalin-related lectins [221,266]. Among the stress inducible cytoplasmic/nuclear lectins identified so far, Nictaba belonging to the Nictaba-related lectins [267], Orysata belonging to the jacalin-related lectins [268], and OrysaEULD1A belonging to the EUL-related lectins [269], all readily interact with high-mannose glycan structures (Table 7). Accordingly, they participate as signaling molecules in the plant response to stress conditions [270].…”
Section: Functions Of Mannose-specific Lectinsmentioning
confidence: 99%